Penggunaan Antibiotik yang Rasional untuk Mencegah Resistensi Antimikroba di SMK Islam Nurul Iman - Annisa Primadiamanti; Cahya Media Kusuma; Chalista Azzahra; Desi Nurjanah; Dia Kurnia Anggraini; Eka Safitri (Institut Nalanda, 2026)
The irrational use of antibiotics is a significant factor in the development of antimicrobial resistance in the community. A low level of knowledge, particularly among adolescents, contributes to the practice of using antibiotics without a prescription and not in accordance with proper guidelines. The objective of this community service activity was to enhance the understanding of pupils at SMK Islam Nurul Iman Lampung Timur, Muara Gading Mas Village, regarding the appropriate use of antibiotics in order to prevent antimicrobial resistance. The method used was health education through interactive lectures, discussions, and the administration of questionnaires before and after the educational session. A total of 30 students participated in this activity. The findings revealed that there was an enhancement in the level of knowledge among students following the educational intervention since the average test result increased from 66.66% to 78.26%. The analysis proved that there was a significant difference between the level of knowledge before and after the educational intervention (p < 0.05).